IDENTIFIKASI BI RATE, INDEKS HARGA SAHAM KOMPOSIT (IHSG), UANG BEREDAR TERHADAP INFLASI DI INDONESIA - Khalid Fauzi Aziz; Roni Yanto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to identify the effect of the BI Rate, the composite stock price index (IHSG), and the money supply on inflation in Indonesia. The research method used for data analysis is the assumption of normality error, multicollinearity assumption, non-autocorrelation assumption, homoscedasticity assumption, multiple linear regression and t test. The type of research used in this research is descriptive quantitative. So that the results of the analysis will be explained according to the data analysis technique used. The results of the determinant coefficient test obtained a value of r which is a reflection of the BI Rate, JCI and Money Supply variables, which are able to explain or explain the inflation variable of 75.23%, the remaining 24.77% is explained by other variables. Based on the results of the t test, it was found that the BI Rate alone significantly affected inflation in the data series from 2005 to 2022. Meanwhile, the JCI and money supply did not significantly affect inflation in the data series from 2005 to 2022. It can be said that not all variables are always significant according to the hypothesis, and the number of years of research also affects it.